1995
DOI: 10.1080/0962029950040204
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors in the Implementation of a Computer Network for English Language Teachers

Abstract: Studies on teacher education networks have unanimously pointed out that networks which allow teachers to share their experience, problems and curriculum materials enhance collegiality and professional growth. This paper reports findings of the implementation of TekNex (Teachers of English Language Education Nexus) which is a teacher education network linking the Teachers of the English Language Education Centre (TELEC) set up at the University of Hong Kong with secondary schools. It points out that for a netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Many researchers have pointed out that despite the potential of CMC for collaboration and for bringing about quality interactions because of its lack of physical and emotional cues, in practice, however, participation by users is often scanty and patchy (see for example Crook, 1994;Light et al, 1997;McAteer et al, 1997;Pearson, 1999). Though explanations like lack of time are often put forward by users for not participating (see for example Tsui, 1995;Tsui & Ki, 1996;Mason & Bacsich, 1998), it has been observed that a skewed participation rate seemed to be the norm, which suggests that something more fundamental is at work (see Tolmie & Boyle, 2000). While a number of studies have made observations of what these factors could be, citing evidence from a small number of respondents, so far, not many empirical studies have been conducted systemically on the dimensions which mediate user participation.…”
Section: Computer Network As Socio-technical Systemsmentioning
confidence: 99%
“…Many researchers have pointed out that despite the potential of CMC for collaboration and for bringing about quality interactions because of its lack of physical and emotional cues, in practice, however, participation by users is often scanty and patchy (see for example Crook, 1994;Light et al, 1997;McAteer et al, 1997;Pearson, 1999). Though explanations like lack of time are often put forward by users for not participating (see for example Tsui, 1995;Tsui & Ki, 1996;Mason & Bacsich, 1998), it has been observed that a skewed participation rate seemed to be the norm, which suggests that something more fundamental is at work (see Tolmie & Boyle, 2000). While a number of studies have made observations of what these factors could be, citing evidence from a small number of respondents, so far, not many empirical studies have been conducted systemically on the dimensions which mediate user participation.…”
Section: Computer Network As Socio-technical Systemsmentioning
confidence: 99%
“…As the majority of TeleNex users were computer novices, the technical hurdle they had to face in using the network was substantial (Tsui, 1995). Several kinds of support were given.…”
Section: Overcoming the Technical Barriermentioning
confidence: 99%
“…There was a social barrier that these teachers needed to overcome in order to participate in network discussions (Tsui, 1995). There was a social barrier that these teachers needed to overcome in order to participate in network discussions (Tsui, 1995).…”
Section: Overcoming the Technical Barriermentioning
confidence: 99%
“…After four months, teachers reported that it was 'very threatening to have their names appearing in the messages, and even more threatening to have their school names appearing as well' (Tsui 1995). These teachers were concerned about perceptions of their personal competence with English, their knowledge about teaching English as a second language and, as a result, the reputation of their schools which might be held by others.…”
Section: Anonymity and Network Participationmentioning
confidence: 99%
“…Subsequently, it was felt that signing off a message as anonymous has an undesirable effect on secrecy and this option was changed to 'An English Teacher'. (Tsui 1995) Data on usage patterns with these options were not presented but Tsui (1995) noted that:…”
Section: Anonymity and Network Participationmentioning
confidence: 99%